1999
DOI: 10.1046/j.1365-2591.1999.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of an odontogenic cutaneous sinus tract

Abstract: A 22-year-old female presented with a draining sinus tract on her left cheek. The tooth responsible was examined clinicopathologically. On clinical examination, the mandibular left first molar tooth was restored with an amalgam filling. Radiographic examination revealed base or pulp capping material below the restoration and a radiolucent periapical lesion surrounding the distal root apex. Conservative non-surgical root canal treatment was performed; 10 months later, the sinus had healed completely and the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…To make the correct diagnosis, obtaining the clinical and medical history, especially of any past episodes of dental pain, from the patient is important (Nakamura et al . ). Pulp tests and periradicular diagnostic testing should be performed on any suspected teeth and adjacent teeth (Gupta et al .…”
Section: Diagnosismentioning
confidence: 97%
See 3 more Smart Citations
“…To make the correct diagnosis, obtaining the clinical and medical history, especially of any past episodes of dental pain, from the patient is important (Nakamura et al . ). Pulp tests and periradicular diagnostic testing should be performed on any suspected teeth and adjacent teeth (Gupta et al .…”
Section: Diagnosismentioning
confidence: 97%
“…Some studies have suggested inserting a probe or an endodontic gutta‐percha point through the sinus tract to obtain radiographs so as to aid the identification of the affected teeth (Nakamura et al . , Pasternak‐Júnior et al . , Gupta et al .…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Fistülün intraoral veya ekstraoral bölgeye açılması dişin bulunduğu bölgeye, enflamasyon tarafından kortikal kemikte oluşan perforasyonun lokalizasyonuna bağ-lıdır. [1][2][3][4] Bakteriyel virülans, hastanın savunma mekanizması, fasiyal bölgedeki dokuların düşük direnci ve kas ataçmanları ile enfekte dişin ilişkisi de fistülün ilerleme miktarını ve yönü-nü etkilemektedir. Eğer dişlerin apikal kısımları maksiller kas bağlantılarının üstünde veya mandibuler kas bağlantılarının altındaysa enfeksiyon ekstraoral bölgeye doğru bir yayılma gösterebilmektedir.…”
Section: Introductionunclassified